Lactate variation in triathletes during a sprint test - García-Cardona, Diana María
The objective of this research is to determine the variation of lactate on triathletes from Quindío, during a sprint test, before and after a developer mesocycle. Regarding materials and methods, 12 male triathletes participated (Age: 30 ± 9 years). Lactate was measured during a sprint test before and after the developer mesocycle. In addition, variables of height, mass, BMI and heart rate were determined. As results, it was found that the lactate concentration did not vary significantly with respect to the measurement before the mesocycle, finding the highest peak post-swim and post-run. Therefore, it can be concluded that the highest lactate concentration achieved was during running, after the mesocycle.